2012
DOI: 10.1080/02786826.2012.661103
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Automotive Nonvolatile Particle Number Emissions within the European Legislative Framework: A Review

Abstract: In 2011, the European Commission introduced a limit for nonvolatile particle number (PN) emissions >23 nm from light-duty (LD) vehicles and the stated intent is to implement similar legislation for on-road heavy-duty (HD) engines at the next legislative stage. This paper reviews the recent literature regarding the operation-dependent emission of PN from LD vehicles and HD engines, and the measurement procedure used for regulatory purposes. The repeatability of the PN method is of the order of 5% and higher sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
148
1
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(159 citation statements)
references
References 147 publications
(227 reference statements)
9
148
1
1
Order By: Relevance
“…With the separation of the volatile particles and the chosen lower particle size detection limit of 23 nm, an important part of the aerosol, possibly relevant for adverse health effects, is neglected (Giechaskiel et al, 2012). Studies indicate that both the solid particle core and/or adsorbed chemical molecules are responsible for adverse health effects (Lovik et al, 1997;Yang et al, 1999;US EPA, 2002).…”
Section: Emission Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the separation of the volatile particles and the chosen lower particle size detection limit of 23 nm, an important part of the aerosol, possibly relevant for adverse health effects, is neglected (Giechaskiel et al, 2012). Studies indicate that both the solid particle core and/or adsorbed chemical molecules are responsible for adverse health effects (Lovik et al, 1997;Yang et al, 1999;US EPA, 2002).…”
Section: Emission Factorsmentioning
confidence: 99%
“…The concern about the potential size dependent effect of particles for adverse health effects stimulated research work characterizing particle number size distribution of exhaust emissions (Giechaskiel et al, 2012). Only a few studies are available calculating particle size dependent emission factors (Birmili et al, 2009, Wang et al, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the California Air Resource Board (CARB) is debating future PM emission regulations for the low-emission vehicle (LEV)-III standards. CARB has revealed that sub-23 nm particles comprise a substantial portion of the total PM emissions from GDI vehicles [5,9,21,29,30]. The primary reason for these controversial findings of differences between the particle measurement programme (PMP) methods and CARB relates to the sensitivity of the sampling and dilution approaches for the secondary particles formed from gaseous precursors [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Engine-out particles consist of combustion-generated solid carbon particles and some organic compounds [7][8][9]18,21]. The solid particles become coated with condensed and adsorbed organic compounds, including unburned hydrocarbons and oxygenated hydrocarbons [8,[25][26][27]29,30]. Particle size distributions are generally classified into three modes: nucleation mode (5 nm < dp < 30 nm), accumulation mode (30 nm < dp < 1000 nm) and coarse mode (1000 nm < dp).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation